Prevalence of and risk factors for cranial ultrasound abnormalities in very-low-birth-weight infants at Charlotte Maxeke Johannesburg Academic Hospital - Azra Ghoor; G Scher; D E Ballot (South African Medical Association, 2017)
Background. Periventricular-intraventricular haemorrhage (IVH) and cystic periventricular leukomalacia (cPVL) contribute to neonatal mortality and morbidity. Low birth weight and gestational age are among the risk factors for IVH and cPVL. Objectives. To assess how many very low birth weight (VLBW) infants had cranial ultrasound screening at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and to determine the prevalence of cranial ultrasound abnormalities. To compare the characteristics and risk factors of those VLBW infants with cranial ultrasound abnormalities to those with normal cranial ultrasound findings. Methods. This was a retrospective case-controlled study of infants <1 500 g admitted to CMJAH from 1 January 2013 to 31 December 2015. Cases were identified as infants with IVH or cPVL. Controls were matched 1:2 based on birth weight and gender. Results. Only 55% (856/1 562) of VLBW infants had undergone cranial ultrasound screening. The final sample included 803 VLBW infants. IVH was identified in 26.7% of cases (n=215; 95% confidence interval (CI) 23.8 - 29.9) and 0.9% had cPVL (n=8; 95% CI 0.5 - 1.9). A total of 197 cases were identified and matched with 394 controls. Antenatal care attendance was lower in the cases (71% v. 79%; p=0.039). Sepsis, ventilation, metabolic acidosis and patent ductus arteriosus were all significantly higher in the cases. The use of antenatal steroids was significantly higher in the grades I - II IVH/no-IVH group v. grades III - IV IVH group (44% v. 25%; p=0.017). Conclusion. The prevalence of IVH in our setting was consistent with that of developed countries. Improving antenatal care, infection control, and adequate early resuscitation could decrease the incidence of IVH and cPVL. All VLBW infants should undergo cranial ultrasound screening